ANXIETY, DEPRESSION, AND SELF-CARE MANAGEMENT AMONG PATIENTS WITH HYPOTHYROIDISM. - Km, Nila; Vd, Mekhana; Nair, Sruthi R (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the study was to assess anxiety, depression, and self-care management among patients with hypothyroidism. Methods: A qualitative descriptive study was done among 65 patients who was diagnosed with hypothyroidism, and the data were collected using structured questionnaire to know about self-care management of hypothyroidism and standardized tool (Hamilton rating scale) for assessing anxiety and depression. Results: The result showed that among 65 subjects, 30 (46.2%) had good self-care management, only 1 (1%) had excellent self-care management, 46.1% had severe anxiety, whereas 4.6% subjects had severe depression. There was a positive association between anxiety and depression with self-care management. Conclusion: Hypothyroidism is now becoming more prevalent in the Indian population. From the results of the study, it is obvious that patients with hypothyroidism are at increased risk of anxiety and depression. Self-care management decreases with an increase in anxiety and depression. Hence, proper management is necessary to reduce the deleterious effect of hypothyroidism on physical as well as mental health.